The Role of Peer Counseling in Assisting Students with Issues at Sint Carolus Penfui Catholic High School, Kupang, Academic Year 2025/2026 - Leo, Leni Marlina; Bere, Maria Theresa Febrianty; Atawolo, Portunantus Mura; Nagul, Wens (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Modern society in the information age presents a great deal of complexity. Such a situation triggers individual adaptation to a very complex society that is increasingly open to the bonds of applicable norms. The impact is that individuals develop behavior patterns that deviate from general norms, by doing as they please for their own benefit and personal interests (individualism), which then interferes with and harms themselves and others. The peer counseling training activity is carried out using methods such as: self-reflection, group discussions, and games. The results of this research indicate that peer counseling training activities for SMAK Cint Carolus students as Young People were conducted over four days, specifically on November 15, 22, 29, and December 6, 2025. The students of SMAK Cint Carolus as Young People come from 3 (three) classes. The number of students from SMAK Cint Carolus participating in this training is 20, consisting of 5 from Class X, 10 from Class XI, and 5 from Class XII.